Targeting Staphylococcus aureus quorum sensing with nonpeptidic small molecule inhibitors - Murray, Ewan J.; Crowley, Rebecca C.; Truman, Alex; Clarke, Simon R.; Cottam, James A.; Jadhav, Gopal P.; Steele, Victoria R.; O’Shea, Paul; Lindholm, Catharina; Cockayne, Alan; Chhabra, Siri Ram; Chan, Weng C.; et al. (American Chemical Society, 2014)
A series of 3-oxo-C12-HSL, tetramic acid, and tetronic acid analogues were synthesized to gain insights into the structural requirements for quorum sensing inhibition in Staphylococcus aureus. Compounds active against agr were noncompetitive inhibitors of the autoinducing peptide (AIP) activated AgrC receptor, by altering the activation efficacy of the cognate AIP-1. They appeared to act as negative allosteric modulators and are exemplified by 3-tetradecanoyltetronic acid 17, which reduced nasal cell colonization and arthritis in a murine infection model.